Thymidine phosphorylase promotes angiogenesis and tumour growth in intrahepatic cholangiocarcinoma. (31st May 2020) - Li, Shuangling; Yang, Hongli; Li, Kun; Fan, Guiling; Deng, Li; Xu, Changqing
Abstract : Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver cancer, and thymidine phosphorylase (TP) is a regulator of angiogenesis. To investigate the biological activities of TP in ICC, we established human cholangiocarcinoma RBE cell lines overexpressing TP or silencing TP. Overexpression of TP enhanced viability, suppressed apoptosis and increased tube formation in human umbilical vein endothelial cells, while downregulation of TP reversed these effects. Moreover, an orthotopic xenograft mouse model of ICC was built to further explore TP's function in ICC in vivo. Histological analysis using H&E, TUNEL and Ki67 staining showed that TP promoted tumour growth and inhibited cell apoptosis. Immunostaining for CD31 revealed an elevation in microvessel density in the presence of TP. Besides, upregulation of TP increased the expression of vascular endothelial growth factor, basic fibroblast growth factor, interleukin‐8 and tumour necrosis factor alpha. In contrast, TP knockdown inhibited tumour growth, suppressed microvessel formation and decreased the expression of angiogenesis‐related proteins. Therefore, we suggest that TP promotes angiogenesis and tumour growth in ICC, which can be a potent therapeutic target for ICC treatment.